Терракотовые алтарики из Херсонеса - Шевченко, А.В. (My University, 1995)
Shevchenko A. V. The Terracota Altars from Chersonesus The notice is dedicated to the group of votive ite ms from Chersonesus – terracotta altars with relief images on walls. Principal attention is paid to the similarity of mythological characters portrayed on altars and also the time of their appearance and existance in Hellenic Chersonesus, The author associates their appearance with animation of bounds with Deloss sanctuary in the III and especially in the II century B. C. and considers Chersonesus as a centre of manufacture of these items for Noth Black-Sea-coast region. The notice is supplied by the cataloque of 19 finds of those items found in Chersonesus.